Abordagem do tema solos com ênfase em sua biodiversidade na educação básica no município de Lavras - MG - Toma, Maíra Akemi (2015)
Soil plays an essential role in sustain the life on Earth. However, the lack of knowledge about soil and its biodiversity have generated many degradation processes and, thus, compromising the performance of their functions. Therefore, to stimulate thought on human attitudes in the conservation of soil ecosystem, this study aimed to introduce and develop the Soil theme, with emphasis on soil biodiversity, in basic education in Lavras county, MG. Thus, the research was conducted in three stages. At first a survey of demands on a continuing course of teacher training was performed and educational materials on the subject were developed; then a course of continuous teacher training was developed and offered; and in the third stage, activities in two elementary schools with two teachers participating in the training course were carried out. It was assumed that the teaching materials produced can assist in teaching in Soils and soil biology, but that should be adjusted according to the availability of materials in the schools and creativity of those involved. It was found that there is a growing and promising demand for different courses of graduate for teachers of basic education or a readjust in the selection process of regular graduation courses, since they are highly exclusive to those outside the academic routine. In addition, it was found that the content of Soils and Soil Biology is likely to be working in primary education, mainly through field activities, group activities and videos.